Analisis Pengaruh Harga, Kualitas Produk, Kualitas Pelayanan, Dan Store Atmosphere Terhadap Keputusan Pembelian Di Tokpatok Telang - Farah Anindra Putri; Anshori, Mochammad Isa (PT. Kreasi Karya Majakata, 2025)
This study aims to analyze the effect of price, product quality, service quality, and store atmosphere on purchasing decisions at Tokpatok Telang. Using a quantitative research method, data were collected from 50 consumers through a Likert scale questionnaire distributed online via Google Forms. The collected data were analyzed using multiple linear regression with SPSS software. The results show that product quality has the most significant positive effect on purchasing decisions, followed by price. Meanwhile, service quality and store atmosphere do not have a significant effect. Specifically, product quality (p = 0.006) and price (p = 0.043) significantly influence purchasing decisions, while service quality (p = 0.809) and store atmosphere (p = 0.888) do not. The regression model explains 63.1% of the variance in purchasing decisions (R² = 0.631), and the classical assumption tests confirm that the data meet the normality, multicollinearity, and homoscedasticity assumptions. These findings suggest that Tokpatok should focus on maintaining high product quality and competitive pricing strategies to strengthen consumer purchase decisions and encourage repeat purchases.